Dynamika aktywności zawodowej a ubezpieczenia społeczne - Balcerowicz-Szkutnik, Maria (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
A fragment of a social form of preventing population from negative effects of unemployment mainly within healthcare is discussed. Main analyses concern an issue of unemployment that is presented in first part of the article. This phenomenon adversely influences functioning of organised social security systems based on insurance that aims at protecting the elderly. An analysis of interconnections within the social issues discussed is of high importance of the social image of the social policy realized by the state.Analysis of changes observed on the labour market in Poland is of a more complete and structural form when - in order to illustrate the phenomenon in question - forecasts of the world population age structure made in the UN Department of Population are applied. These forecast may be successfully used for the analyses of labour markets and vocational activities. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 1, s. 11-21